Price and Location Trump Taste in Influencing Consumer Choices in Indonesia: Harga dan Lokasi menjadi Faktor Utama dalam Mempengaruhi Pilihan Konsumen di Indonesia - Priamitra, Caraka; Indayani, Lilik (Indonesian Journal of Law and Economics Review, 2024)
This study analyzes the impact of taste, price, and location on consumer buying interest in Devil Noodle Ponti Sidoarjo using a descriptive quantitative method. Data were gathered via questionnaires from 100 consumers using accidental sampling, and analyzed with multiple linear regression. The results show that while taste does not significantly affect buying interest, both price and location do. These findings suggest that strategic pricing and convenient location are crucial for attracting customers in the specialty noodle market. This research provides valuable insights for marketing strategies in the food industry. Highlights: 1. Taste does not significantly impact consumer buying interest.2. Price and location significantly influence purchasing decisions.3. Strategic pricing and location are crucial for attracting customers. Keywords: Consumer Buying Interest, Taste, Price, Location, Marketing Strategy